Establishment of minimally invasive ventral hernia repair with extraperitoneal mesh placement in a primary care hospital using the robotic platform - Bauer, Katrin; Heinzelmann, Frank; Vogel, Robert; Büchler, Peter; Mück, Björn (Frontiers in Surgery, 2022)
Background: The progressive availability of robotic surgical systems opens new perspectives in abdominal wall surgery due to excellent visibility and dexterity of instruments. While complex hernias until today were treated primarily through an open access, we evaluated if this promising technology is suitable for treating the entire spectrum of a hernia center, including complex hernias. Material/Methods: In 2017, minimally invasive hernia surgery with extraperitoneal mesh placement was started in Kempten hospital. Since 2019, a Da Vinci X system has been available for this purpose. In order to observe the process of transition we retrospectively analyzed all patients who underwent ventral hernia repair in the department of general and visceral surgery at our hospital between January 2016 and December 2020 and were indicated for mesh implantation. Results: In 2016, the percentage of minimally invasive procedures was 37,3%. In all of these cases an intraperitoneal mesh was implanted into the abdominal cavity. Open surgery was performed in 62,7%, of which an a retromuscular mesh was implanted in 75,7%, an intraperitoneal mesh in 21,6%, and an onlay mesh in 2,7%. In 2020, minimally invasive surgery accounted for 87.5%, of which 85,7% were performed robotically and 14,3 laparoscopically. In 94.3% of these minimally invasively treated patients the mesh was implanted in extraperitoneal position (75.8% in retromuscular and 24.2% in preperitoneal position). The percentage of complex hernias increased from 20,3% to 35,0% during the same period. Conclusion: The majority of ventral hernia procedures can be performed safely using the robot in a minimally invasive technique with extraperitoneal mesh placement without leading to an increase in complications. Robotically-assisted hernia repair is a promising new technique that is also practical for complex hernias.